Impact of long ocean waves on wave height retrieval from SAR altimetry data. Issue 6 (15th September 2018) - Moreau, T.; Tran, N.; Aublanc, J.; Tison, C.; Le Gac, S.; Boy, F.
Abstract: SAR altimetry is a new high-resolution operation mode exploited in new-generation altimeter missions, such as Sentinel-3. It takes advantage of its enhanced along-track resolution to make measurements of sea surface height variations in much greater detail than what can be achieved with conventional low resolution instruments (e.g. the Jason-3 altimeter). However, contrary to what is observed for conventional altimetry, long-wavelength ocean waves of a few hundred meters (swell and extreme wind waves) are no longer fully imaged in the instrument ground cells, and SAR waveforms have distorted shapes in such wave conditions. This affects the final retrieval of significant wave height (SWH). This paper analyzes the impact of long ocean waves on SAR-mode data by using both Cryosat-2 measurements and simulated data. Results from these two approaches are in good agreement and show that the estimated parameters from SAR-altimetry waveforms are particularly noisy under long-wave conditions and also biased when compared with conventional altimetry data. Additionally, we found evidence that these impacts are different between the two directions (along and cross-track directions) due to the asymmetry of the SAR-altimetry footprint. Simulations indicate that statistics of sea surface elevations within the SAR-altimetry footprint deviate from Gaussian behavior. The assumption commonly used for ocean retracking algorithms is therefore inaccurate. The sensitivity of SAR-mode altimetry data to long waves is a key issue for the ocean altimetry community, which is concerned to ensure the continuity of high-quality time series of the global sea-surface topography in future years. This is not only an issue for these new-generation radar altimeters (Sentinel-3 and Sentinel-6) but also for all innovative techniques or processing methodologies capable of providing higher spatial resolution of the ocean surface.